Analisis Faktor Reinforcing Pada Pemeriksaan Payudara Sendiri (SADARI) - Dede, Dede Waslia (JURNAL KESEHATAN KARTIKA, 2019)
Breast cancer is a major issue of women's health in the world, especially in developingcountries which have limited resources such as in Indonesia. The reason is because of thelack of an effective screening program to detect pre-cancerous and cancer conditions at earlystage including treatment before a further invasive process. Early detection of breast cancerneeds to be done to reduce mortality rate. Breast self-examination can find breast cancer up to75-85% if done regularly. Willingness to perform breast self-examination is one form ofbehavior which is influenced by many factors,one of which is reinforcing. The aim of theresearch is to identify the relationship between reinforcing factors and breast selfexamination(BSE). The method used is a quantitative with a cross sectional approach. Thepopulations were reproductive age women with a sample of 120 people by random samplingtechnique. Data collection was done through direct interview using questionnaire. The resultsconcluded that from 120 respondents, most respondents (74.2%) perform breast selfexamination.The reinforcing factors associated with breast self-examination are friendssupport (Pvalue 0,000), husband/ family support (Pvalue 0,000), and health personnel support(Pvalue 0,000).The most related reinforcing factor is husband / family support.